2019
DOI: 10.1007/s12020-018-01834-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone on hepatic insulin sensitivity and glucose effectiveness in healthy older adults

Abstract: Purpose: Growth hormone (GH) replacement decreases insulin sensitivity in healthy individuals. However, the effects of GH on organ-specific insulin sensitivity and glucose effectiveness are not well characterized. The purpose of this study was to evaluate the effects of GH administration for 26 weeks on muscle and hepatic insulin sensitivity and glucose effectiveness in healthy older individuals. Methods: This report is from a 26-week randomized, double-blind, placebo-controlled parallelgroup trial in healthy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Patients with acromegaly have an increased glucose turnover, as GH increases hepatic glucose production by increasing glycogenolysis (17). Chronic GH administration impairs insulin sensitivity in the liver, thereby reducing the ability of insulin to suppress gluconeogenesis and glucose output (12, 32, 61).…”
Section: Pathophysiology Of Insulin Resistance In Acromegalymentioning
confidence: 99%
“…Patients with acromegaly have an increased glucose turnover, as GH increases hepatic glucose production by increasing glycogenolysis (17). Chronic GH administration impairs insulin sensitivity in the liver, thereby reducing the ability of insulin to suppress gluconeogenesis and glucose output (12, 32, 61).…”
Section: Pathophysiology Of Insulin Resistance In Acromegalymentioning
confidence: 99%
“…Moreover, the mechanisms promoting increasing concentrations of SHBG with advancing age is yet to be elucidated, however, a plausible theory exists (Figure 4). Since growth hormone (GH) induces hepatic IR (Forrest et al, 2019; Mercado & Ramirez‐Renteria, 2018), resulting in reduced SHBG synthesis, a reduction in GH concentrations due to aging (Chahal & Drake, 2007) may improve hepatic insulin sensitivity and therefore, increase SHBG synthesis (Thaler et al, 2015). Hence, the gradual increase in SHBG concentrations in men as they age.…”
Section: Discussionmentioning
confidence: 99%
“…However, some have reported that GH treatment reduced insulin sensitivity [ 24 ]. In healthy older subjects, GH administration for 26 weeks impaired insulin sensitivity in the liver, but not in skeletal muscle [ 25 ]. Although we considered that the development of type 2 diabetes was not caused by GH treatment in this case, because no abnormal blood glucose levels were found during the GH treatment and six years had already passed after the end of the treatment, long-term GH treatment might have been involved in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%